Growth and Survival of Seabass (Lates calcarifer) Cultured under Different Salinity Levels and Tank Colours - Manijo; Ateng Supriatna; Lilik Sulistyowati (Journal of Aquaculture Science, 2025)
This study investigated the interaction between salinity and container colour on survival, growth, and feed conversion ratio in barramundi (Lates calcarifer). This study used a Randomised Block Design (RCD), with juvenile sea bass (2-3 g weight, 5-6 cm length) stocked into a 70 litre aquarium. The study was conducted with a combination of three salinity levels (0, 15, and 30 ppt) and three container colours (blue, black, and orange). Each treatment consisted of 35 juveniles fed 40% crude protein pellets (0.7-1 mm) at 7% of biomass, three times a day for 28 days. There was a significant interaction between salinity and container colour on L. Calcarifers growth. Blue containers supported better weight gain at all salinity levels. Meanwhile, orange containers reduced the negative impact of high salinity on growth. Although, this interaction was not significant for length growth or feed conversion.